INVITRO STUDY OF ASPERGILLOSIS AND THE EFFECT OF SELECTED TRADITIONAL PLANTS AGAINST THE PATHOGENIC FUNGAL ORGANISM OF ASPERGILLUS FUMIGATES: Pharmaceutical Science-Pharmacology - VISVANATHAN. S; REENA T; POOJA MOHAN; ANCY JUSTIN J.K (International Journal of Life Science and Pharma Research, 2022)
The present study was designed to obtain the information about the allergenic proteins present in Aspergillus fumigates from mycelial extracts. A. fumigatus was isolated from the decayed vegetables and mass cultivated done for 14 days. The experimental crude extracts were prepared from A. fumigatus, estimated the proteins by ammonium precipitation method. The fungal spores were subjected to experimental rabbit and the serum sample was collected from the infected rabbit for further analysis such as the immunological techniques are Immuno-electrophoresis, single radial immuno diffusion and western blotting technique were completed for determined the specificity and molecular weight of the specific antigen present in the fungal sample affected in experimental rabbit. The current result showed the presence of the specific antigen on mycelial extract against antiserum. Through, the immune blot technique the molecular weight of antigen from mycelial extract contained 42k Da compared with molecular weight of different antigenic protein obtained by SDS-PAGE. The effect of various plant extract were observed through Kirby Baeyer technique and by direct intake of the infected rabbit. The Coriandrum sativum showed greater effect against A.fumigatus. Although, among the six plants C. sativum possessed significant effect against the experimental pathogens. So the important phytoactive compounds are elucidated by the GCMS analysis as well as the following important bioactive constituents were identified such as 1 1 - t e t r a d e c e n o i c a c i d , c a r p i c a c i d ( 1 2 . 7 % ) , u n d e c y l a l c o h o l ( 6 . 4 % ) , t r i d e c e n o i c a c i d ( 5 . 5 % ) , u n d e c e n o i c a c i d ( 7 % ) . T h e p r e s e n c e o f t r i d e c e n o i c a c i d w a s f o u n d t o b e t o o l o w asphenols, fixed fats and oils also been noted. Hence, the present study was concluded that the medicinal plant of C. sativum comprised superior antifungal consequences against the pathogenic fungi of A. fumigates. Therefore, C. sativum is potential used for pharmaceutical purpose for arrest or destroy the aspergillosis.